Effects of Yoga on Anxiety and Autonomic Function in Panic Disorder Patients - Mrigendra Amatya, Dr (International Journal of Pharmaceutical & Biological Archive, 2012)
Effects of Yoga on Anxiety and Autonomic Function in Panic Disorder Patients